The Effects of Monetary Policy Shocks on Income Inequality Across U.S. States. Issue 3 (16th March 2020) - Siami‐Namini, Sima; Lyford, Conrad; Trindade, A. Alexandre
Abstract : Using a time series cross‐state panel data of 50 U.S. states and the District of Columbia (DC) over the period of 1959 through 2015, this article intends to assess the direct and indirect effects of contractionary monetary policy shocks on income inequality through interest rate and consumer price index (CPI) inflation channels. To address this, the authors examine two possible linear and non‐linear relationships between inflation and income inequality and between gross domestic product (GDP) and income inequality. Using various measures of income inequality, the results of the pooled model and the individual fixed effect model show that CPI inflation positively and interest rate negatively affect all measures of income inequality in linear regression. The results confirm the existence of the non‐linearity relationship between inflation and income inequality as well as the Kuznets inverted "U‐shaped" hypothesis between GDP and income inequality. The results of linear and non‐linear regressions show that the DC and the state of Ohio are better off and worse off than the state of Alabama as baseline of models, respectively. The impulse response functions (IRFs) for the individual panel vector autoregressive (PVAR) models show that income inequality could be reduced by implementing contractionary monetary policy through interest rate channel in the short run and increased persistently pursuing contractionary monetary policies via inflation channel in the long run.